The Image of Municipalities - Evstratova, Tatiana A. (2022)
Purpose of the study: The aim of this study is to investigate the image of municipalities and also to determine the things that give the city a positive image of the territory. Methodology: The theoretical and methodological basis of the study is the ideas and paradigms that were developed in the works of leading domestic sociologists, cult urologists, economists, and marketers. The applied individual methods include comparative analysis, typology, classification method, questionnaire, method of analysis of social factors and events Results: The Program of socio-economic development must be amended in the form of a subprogram for the formation of a positive image of the municipality of Chekhov, since today there are no projects or programs aimed at creating a positive image of the municipality to one degree or another, its popularization and perception among the local population and among tourists. Moreover, information support of the main assets of the municipality of Chekhov (information about the advantages of the territory, photographs and advertising leaflets) in social networks, the media, on the Internet, that is, marketing of historical and cultural heritage with a priority on the work of A.P. Chekhov Applications of this study: The formation of a favorable image is of fundamental importance primarily for residents of the municipality. It affects the creation and support of social optimism among the population, trust in the authorities and confidence in the future. Novelty of the study: The image of the municipality is formed from the priority elements of its structure and a set of certain factors of development and promotion of the territory. So, the novelty of this study is to asses this image in modern life